Combination Moringa oleifera Extract and Ifalmin as Potential Formulation of Preventing Inflammation in Diabetic Mice Model - Nilamsari, Ruri Vivian; Adharini, Wahyu Isnia; Lestari, Noviana Dwi; Tsuboi, Hideo; Rifa'i, Muhaimin (Graduate School, Universitas Brawijaya, 2020)
In Indonesia, the prevalence of diabetes mellitus hits 6.2%, making Indonesia one of the top ten diabetes mellitus countries. Efforts to prevent and treat people with diabetes in Indonesia are required to minimize that as well. One is through treatment with local herbal products such as Moringa oleifera (MO) and Toman fish extract (Channa micropeltes), called Ifalmin. The aim of this research is to investigate the potential role of a combination of Extract Moringa oleifera and Ifalmin to reduce inflammation in diabetes conditions. Diabetic mice were done by Streptozotocin (STZ) induction with a single-dose 145 mg.kg-1.Then, diabetic mice were given an oral treatment of combination MO extract and Ifalmin for 14 days. In this experiment combinations of MO extract and Ifalmin are divide into 3 dose, There are: dose 1 (800 mg.kg-1 : 800 mg.kg-1), dose 2 (650 mg.kg-1 : 650 mg.kg-1), and dose 3 (800 mg.kg-1 : 650 mg.kg-1). Immune cells originate from the spleen are stained by immunofluorescence antibodies and analyzed by flow cytometry with BD Cellquest ProTM software. The results showed an increase of expression pro-inflammatory cytokines IL-1β and IL-6 in diabetic mice compared to normal control. Only dose 1 and dose 2 has shown the capability to reduce the expression of IL-1β in diabetic mice. But, the combination of MO and Ifalmin has an antagonist effect on the expression of IL-6. The inhibitory mechanism can be assumed by the action of antioxidant compounds (Flavonoids and Alkaloids) in MO and Albumin compound in Ifalmin. Those combination act as exogenous antioxidant that help endogenous inside the body. A combination of MO extract and Ifalmin with a certain dosage was able to decrease proinflammatory cytokines IL-1β on the cells involved in innate immunity.